Recent advances in prevention, detection and treatment in prosthetic joint infections of bioactive materials - Xie, Hongbin; Liu, Yubo; An, Haoming; Yi, Jiafeng; Li, Chao; Wang, Xing; Chai, Wei (Frontiers in Bioengineering and Biotechnology, 2022)
Prosthetic joint infection (PJI) is often considered as one of the most common but catastrophic complications after artificial joint replacement, which can lead to surgical failure, revision, amputation and even death. It has become a worldwide problem and brings great challenges to public health systems. A small amount of microbe attaches to the graft and forms a biofilm on its surface, which lead to the PJI. The current standard methods of treating PJI have limitations, but according to recent reports, bioactive materials have potential research value as a bioactive substance that can have a wide range of applications in the field of PJI. These include the addition of bioactive materials to bone cement, the use of antibacterial and anti-fouling materials for prosthetic coatings, the use of active materials such as bioactive glasses, protamine, hydrogels for prophylaxis and detection with PH sensors and fluorescent-labelled nanoparticles, and the use of antibiotic hydrogels and targeting delivery vehicles for therapeutic purposes. This review focus on prevention, detection and treatment in joint infections with bioactive materials and provide thoughts and ideas for their future applications.